Distributed MIMO CW Radar for Locating Multiple People and Detecting Their Vital Signs - Juan, Pin-Hsun; Chueh, Chi-Yuan; Wang, Fu-Kang (IEEE transactions on microwave theory and techniques, 2023)
The distributed-multiple-input multiple-output (MIMO) continuous-wave (CW) radar with low-intermediate frequency (low-IF) receiver that is proposed in this work uses uniform linear array (ULA) antennas to estimate the direction of arrival (DOA) of subjects and recover Doppler signals by the digital beamforming (DBF) technique. Without using any modulation bandwidth, the location of multiple subjects can be determined from the known antenna positions and the estimated DOAs. This work proves that the Doppler-weighted method improves the extraction of the initial phase of the baseband signal. With respect to the recovery of each subject's vital signs, the modified-DBF is utilized to separate individual Doppler signals while nullifying interference. The frequency estimation algorithm (FEA) is used to improve the Doppler frequency and angular resolution by 50% and 44%, respectively, in the detection of two closely spaced moving metal plates. Finally, the presented system is experimentally validated by determining the locations and vital signs of people sitting side-by-side. The estimated DOA and position errors were less than 3.3° and 10 cm, respectively. With a 25 s sensing period, the errors in the measured respiration rates (RRs) and heart rates (HRs) were less than 1.2 breath/min and 3 beats/min, respectively.